Ancient worlds in digital culture - Clivaz, Claire. (Digital Biblical Studies, 2016)
The volume presents a selection of research projects in Digital Humanities applied to the "Biblical Studies" in the widest sense and context, including Early Jewish and Christian studies, hence the title "Ancient Worlds". Taken as a whole, the volume explores the emergent Digital Culture at the beginning of the 21st century. It also offers many examples which attest to a change of paradigm in the textual scholarship of "Ancient Worlds": categories are reshaped; textuality is (re-) investigated according to its relationships with orality and visualization; methods, approaches and practices are no longer a fixed conglomeration but are mobilized according to their contexts and newly available digital tools.